Anti-Inflammatory Effects and Mechanisms of Dandelion in RAW264.7 Macrophages and Zebrafish Larvae - Li, Wenju; Luo, Fulong; Wu, Xiaohui; Fan, Bei; Yang, Mingran; Zhong, Wu; Guan, Dongyan; Wang, Fengzhong; Wang, Qiong (Frontiers in Pharmacology, 2022)
Dandelions (Taraxacum spp.) play an important role in the treatment of inflammatory diseases. In this study, we investigated the anti-inflammatory effects of Dandelion Extract (DE) on LPS-induced RAW 264.7 macrophages and copper sulfate (CuSO4)-induced zebrafish larvae. DE at 75 μg/mL was not toxic to RAW264.7 cells as detected by cell viability assay and inhibited LPS-induced cell morphological changes in inverted microscopy analysis. DE at 25 μg/mL had no toxicity to zebrafish larvae in survival observation. DE reduced the production of nitric oxide (NO) in LPS-induced RAW264.7 cells by enzymatic standard assay. DE reduced LPS-induced ROS production and apoptosis in RAW264.7 cells in fluorescence microscopy detection. Furthermore, DE reduced CuSO4-induced ROS production and neutrophil aggregation in zebrafish larvae. Flow cytometry results showed that DE relieved the LPS-induced cell cycle arrest. RT-PCR showed that DE decreased the expression levels of M1 phenotypic genes iNOS, IL-6 and IL-1β, DE increased the phenotypic conversion levels of M2 phenotypic genes IL-10 and CD206 in LPS-induced RAW264.7 cells. In addition, DE reduced the expression levels of iNOS, TNF-α, IL-6 and IL-10 in CuSO4-induced zebrafish larvae. Collectively, the results of this study suggest that DE reduces the LPS-induced inflammatory response by regulating the polarization and apoptosis in RAW264.7 cells, DE also reduces the CuSO4-induced inflammatory response in zebrafish larvae.